Assessing the Passenger Load of Urban Bus Services in Southern States Peninsular of Malaysia - Bakar M.F.A.; Norhisham S.; Khebir M.I.A.; Saad N.M.; Azlan N.N.I.M.; Shkuri N.S.M.; Yukawa S.; Syamsir A. (Springer Science and Business Media Deutschland GmbH, 2023)
Bus transportation; Buses; Traffic congestion; Urban transportation; Amounts of traffics; Bus services; Classifieds; Malaysia; Passenger loads; Quality-of-service; Southern state; Urban areas; Urban bus; Urban bus service; Quality of service